FORECASTING THE DEVELOPMENT OF ACUTE POISONING IN AGRICULTURAL WORKERS USING PESTICIDES IN THE SYSTEM OF CHEMICAL PROTECTION OF POTATOES. - O.О. Novohatska (Bogomolets National Medical University, 2017)
According to the WHO, among the main causes of non- infectious diseases, a group of chemical factors are distinguished, the main part of which falls on pesticides. Namely, non-compliance with the rules of pesticides application leads to the risk of occupational diseases development among workers. In modern conditions, high and stable crops of agricultural cultures cannot be obtained without the chemical means of plant protection application. The purpose of our work was to predict the development of acute poisoning in agricultural workers using pesticides in the system of chemical protection of potatoes. Materials and methods of research. In order to assess the impact on the agricultural sector workers of the studiedsubstances and formulations, the coefficients of the possible inhalation poisoning (CPIP), the coefficients ofpesticides action selectivity at inhalation exposure (CASing) and the coefficients of pesticides action selectivity at dermal exposure (CASderm) were calculated on their basis. Calculated CASingvalues were (102,3 - 1646,1) and indicate a rather high selectivity of their action, which indicates a rather low probability of acute toxic effectsoccurrence.Except for thiametoxam, flufenacet, metrubuzin, mancozeb, CASingof which were 14,7-61,6, which indicates the low selectivity of their action and the high probability of acute toxic effects occurrence entering the farm workers'organism. Calculated CASdermvalues for all active substances were in the range of 102,9-10288,1, which indicates a rather high selectivity of their action and a low probability of poisoningsoccurrence. By the CPIP value <0,5 - all investigated active substances and formulations on their basis belong to the 4th class of danger in accordance with State Standards 8.8.1.002-98. The obtained results indicate the necessity of using personal protective equipment by workers during the application of the studied pesticides and the mandatory observance of agrotechnical regulations.